Sosialisasi Gadget Sehat Untuk Membimbing Anak-Anak dalam Penggunaan Teknologi Dengan Bijak - Ali Mahdi, Azra; Utami, Nabila; Syahrani, Nur; Br. Ginting, Siti Salamah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This research aims to examine community service activities in an effort to realize healthy and wise use of gadgets among children in Bandar Magodang Village, Bintang Bayu District. Stages include planning, education, training and mentoring children. The service team from the Mathematics Education Study Program, North Sumatra State Islamic University carried out outreach on 19-20 August 2023, involving 10 village children. The results include preparation, coordination with related parties, outreach materials, and implementation activities. The research also looked at the positive and negative impacts of gadget use on children's development, emphasizing the need to limit gadget use to maintain physical and mental health. Activity documentation is available for further reference.